Современные методы управления качеством в литейном производстве - Пелых, С. Г.; Пономаренко, Ольга Ивановна (Белорусский национальный технический университет, 2002)
In the article there is made analysis of using of the cybernetic methods and also are determined the peculiarities of the solution of problems on quality control of castings in foundry.
New methods of quality control in foundry
Keywords: кибернетика; электрический режим плавки; чугун серый; автоматизированные системы управления производством